Freight Transport Costs Model Based on Truck Fleet Operational Parameters - Kulović, Mirsad (Promet - Traffic&Transportation, 2004)
The road freight transport costs are a function of numerousfactors that could be grouped according to their characteristicsand level of utilization of company's technical and human potential.The different input prices, product characte1istics, truckconfiguration, geographical characteristics, road conditions,and driving characteristics make it very difficult to estimate thecurrent transportation costs for a particular company. To investigatethe main factors that may affect road freight transportcosts, it is useful to analyze the influence of truck fleet operationalparameters on these costs. This paper desc1ibes freighttransport costs model based on tntck fleet operational parameters.The explanation of the model is given through a practicalexample. The model enables changes of input parameters andreflects the influence of different management decisions whichhave an impact on transportation costs.